Left ventricular mechanical dispersion predicts arrhythmic risk in mitral valve prolapse. Issue 14 (12th February 2019) - Ermakov, Simon; Gulhar, Radhika; Lim, Lisa; Bibby, Dwight; Fang, Qizhi; Nah, Gregory; Abraham, Theodore P; Schiller, Nelson B; Delling, Francesca N
Abstract : Objective: Bileaflet mitral valve prolapse (MVP) with either focal or diffuse myocardial fibrosis has been linked to ventricular arrhythmia and/or sudden cardiac arrest. Left ventricular (LV) mechanical dispersion by speckle-tracking echocardiography (STE) is a measure of heterogeneity of ventricular contraction previously associated with myocardial fibrosis. The aim of this study is to determine whether mechanical dispersion can identify MVP at higher arrhythmic risk. Methods: We identified 32 consecutive arrhythmic MVPs (A-MVP) with a history of complex ventricular ectopy on Holter/event monitor (n=23) or defibrillator placement (n=9) along with 27 MVPs without arrhythmic complications (NA-MVP) and 39 controls. STE was performed to calculate global longitudinal strain (GLS) as the average peak longitudinal strain from an 18-segment LV model and mechanical dispersion as the SD of the time to peak strain of each segment. Results: MVPs had significantly higher mechanical dispersion compared with controls (52 vs 42 ms, p=0.005) despite similar LV ejection fraction (62% vs 63%, p=0.42) and GLS (−19.7 vs −21, p=0.045). A-MVP and NA-MVP had similar demographics, LV ejection fraction and GLS (all p>0.05). A-MVP had more bileaflet prolapse (69% vs 44%, p=0.031) with a similar degree of mitral regurgitation (mostly trace or mild in both groups) (p>0.05). A-MVP exhibited greater mechanical dispersion when compared with NA-MVP (59 vs 43 ms, p=0.0002). Mechanical dispersion was the only significant predictor of arrhythmic risk on multivariate analysis (OR 1.1, 95% CI 1.02 to 1.11, p=0.006). Conclusions: STE-derived mechanical dispersion may help identify MVP patients at higher arrhythmic risk.